Comparing single- and multi-post labeling delays for the measurements of resting cerebral and hippocampal blood flow for cerebrovascular testing in midlife adults - Decker, Kevin P.; Sanjana, Faria; Rizzi, Nick; Kramer, Mary K.; Cerjanic, Alexander M.; Johnson, Curtis L.; Martens, Christopher R. (Frontiers in Physiology, 2024)
Objectives: To assess the reliability and validity of measuring resting cerebral blood flow (CBF) and hippocampal CBF using a single-post-labeling delay (PLD) and a multi-PLD pseudocontinuous arterial spin labeling (pCASL) protocol for cerebrovascular reactivity (CVR) testing.: 25 healthy, midlife adults (57 ± 4 years old) were imaged in a Siemens Prisma 3T magnetic resonance imaging (MRI) scanner. Resting CBF and hippocampal CBF were assessed using two pCASL protocols, our modified single-PLD protocol (pCASL-MOD) to accommodate the needs for CVR testing and the multi-PLD Human Connectome Project (HCP) Lifespan protocol to serve as the reference control (pCASL-HCP). During pCASL-MOD, CVR was calculated as the change in CBF from rest to hypercapnia (+9 mmHg increase in end-tidal partial pressure of carbon dioxide [PETCO2]) and then normalized for PETCO2. The reliability and validity in resting gray matter (GM) CBF, white matter (WM) CBF, and hippocampal CBF between pCASL-MOD and pCASL-HCP protocols were examined using correlation analyses, paired t-tests, and Bland Altman plots. Results: The pCASL-MOD and pCASL-HCP protocols were significantly correlated for resting GM CBF [r = 0.72; F (1, 23) = 25.24, p < 0.0001], WM CBF [r = 0.57; F (1, 23) = 10.83, p = 0.003], and hippocampal CBF [r = 0.77; F (1, 23) = 32.65, p < 0.0001]. However, pCASL-MOD underestimated resting GM CBF (pCASL-MOD: 53.7 ± 11.1 v. pCASL-HCP: 69.1 ± 13.1ml/100g/min; p < 0.0001), WM CBF (pCASL-MOD: 32.4 ± 4.8 v. pCASL-HCP: 35.5 ± 6.9 ml/100g/min; p = 0.01), and hippocampal CBF (pCASL-MOD: 50.5 ± 9.0 v. pCASL-HCP: 68.1 ± 12.5 ml/100g / min; p < 0.0001). PETCO2 increased by 8.0 ± 0.7 mmHg to induce CVR (GM CBF: 4.8 ± 2.6%; WM CBF 2.9 ± 2.5%; and hippocampal CBF: 3.4 ± 3.8%).Our single-PLD pCASL-MOD protocol reliably measured CBF and hippocampal CBF at rest given the significant correlation with the multi-PLD pCASL-HCP protocol. Despite the lower magnitude relative to pCASL-HCP, we recommend using our pCASL-MOD protocol for CVR testing in which an exact estimate of CBF is not required such as the assessment of relative change in CBF to hypercapnia.